Hegel’s Twofold Critique of Empiricism: Cognition, Ontology and the Question of Universality - Stein, Sebastian (Revista Eletrônica Estudos Hegelianos, 2016)
ABSTRACT: Hegel’s seemingly contradictory assessment of empiricism can be rendered consistent if one distinguishes between two ways in which he interprets it: Firstly, as a theory of cognition and secondly, as a theory of ontological truth. While Hegel argues that the former undermines itself due to its inability to establish the universal and necessary validity of its own perspective, he praises the latter for defending the irreducibility of particularity. Still, from Hegel’s own stance, a successful notion of ontological truth must accommodate what empiricism lacks: A dynamic notion of universality that forms a negative unity with particularity, in which both moments are acknowledged but neither is prioritised. Hegel calls this unity ‘the concept’ and deduces his own notion of cognition from it, thus equipping it with the universal and necessary status that he finds empiricism’s notion of cognition unable to account for.